(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
Mongolian herders are particularly vulnerable to climate change, as their livelihoods depend heavily on livestock production. Understanding the effects of climate hazards such as drought and dzud is crucial for planning and implementing the appropriate responses and effective adaptive measures. In this research, risk is defined as the potential for adverse consequences for herders due to hazardous climatic conditions, and is explained through 4 components including climate hazard, exposure, vulnerability, and response. The purpose of this study is to assess climate hazard risks of herders at the county (soum) level and explore the varying contributions of risk components. Based on a literature review and data availability, 15 factors of risk were selected including temperature and precipitation change, drought and dzud frequency, pasture use index, livestock loss, ratio of seasonal pastureland, water availability, poverty, dependency ratio, education, bank savings, prepared hay and forage, barns, and index-based livestock insurance. Principal Component Analysis (PCA) was used to aggregate the factors within 4 components of risk, and the composite risk index (RI) was calculated using the principal component scores at the soum level in Bayankhongor, Khovd, and Dundgovi provinces of Mongolia. The average RI was 19.2 in Bayankhongor, 14.2 in Khovd, and 17.0 in Dundgovi province. The results highlight the spatial heterogeneity of risk, emphasizing that the northern soums of Khovd and Bayankhongor, and the northeastern soums of Dundgovi are particularly susceptible to climate-related hazards. On the other hand, better hay and forage preparation in Khovd province contributed to its lower overall risk index. Enhancing long-term preparedness measures, such as hay and forage preparation and barn availability, alongside social and financial support mechanisms for vulnerable herder households is crucial for strengthening resilience.